Unfolding the blockchain era: Timeline, evolution, types and real-world applications. (November 2022) - Arooj, Ansif; Farooq, Muhammad Shoaib; Umer, Tariq
Abstract: Blockchain technology is based on a series of time-stamped and decentralized immutable records without third-party involvement. Since the infancy of the term, it has attained attention from academic researchers and industrial contributors, globally. The extensive characteristics of blockchain have created new investigation domains in multiple industries including finance, medical, education, governance etc. In this study, we have conducted the systematic literature mapping to collect all relevant research in the field of blockchain since the inception of this exclusive paradigm and presented a comprehensive assessment and analysis on the extracted research papers in a systematic manner. We have rigorously reviewed the relevant research papers found in the literature for understanding the state of the art techniques, methodologies and, applications of using blockchain in different industries. Moreover, we also have presented the evolution and future insights on the use of blockchain in several real-world applications and also consolidated the blockchain into different high level technical and applied perspectives.